The correlation between rat retinal nerve fiber layer thickness around optic disc by using optical coherence tomography and histological measurements - Ju-Fang Huang Hui-Min Yu Lei Shang Ruo-Fei Ma Ngobe Akume Cynthia Yan-Qun Cao Jia Luo Le-Ping Zeng Dan Chen Kun Xiong (国际眼科杂志：英文版, 2013)
·AIM: To explore the correlation between the retinal nerve fiber layer (RNFL) thickness by using optical coherence tomography (OCT) and by histological measurements in normal adult rats and optic nerve transected rats. · METHODS: The RNFL thickness of 36 rats was scanned in a circle 3.46mm far from the optic disc by OCT. The two experimental groups were the normal group ( =20 rats) and the optic nerve transected group ( =16 rats). The latter group included 4 groups ( =4 /group) surviving for 1 day, 3, 5 and 7 days. Then the RNFL thickness of the same retina area was also measured by NF -200 immunohistochemical staining method. Linear regression was used to analyze the correlation between the data obtained from these two methods. ·RESULTS: The RNFL thickness of normal right eyes around optic disc by OCT was 72.35 ±5.71μm and that of the left eyes was 72.65 ±5.88μm ( =0.074). The RNFL thickness of the corresponding histological section by immunohistochemistry was 37.54 ±4.05μm (right eyes) and 37.38 ±4.23μm (left eyes) ( =0.059). There was a good correlation between the RNFL thickness measured by OCT and that measured by histology (R 2 =0.8131). After optic nerve transection, the trend of the RNFL thickness was thinner with the prolonged survival time. The correlation of the thickness detected by the above two methods was approximately (R 2 =0.8265). Value of the RNFL thickness in rats around optic disc measured by OCT was obviously higher than that measured by common histological measurement in normal adult rats and optic nerve transected rats. ·CONCLUSION: The RNFL thickness measured by OCT has a strong correlation with that measured by histological method. Through OCT scanning, we found that the thickness of RNFL gradually becomes thinner in a time-dependent manner.